Detection and Characterization of Rotavirus G and P Types from Children Participating in a Rotavirus Vaccine Trial in Belém, Brazil - JDP Mascarenhas; AC Linhares; YB Gabbay; JPG Leite (Memorias do Instituto Oswaldo Cruz, 2002)
This study sought the characterization of rotaviruses in a trial with a tetravalent rhesus-human rotavirus vaccine in Belém, Brazil in children who received three doses of vaccine or placebo in the 1st, 3rd and 5th months of life. Rotavirus electropherotypes, subgroups, G serotypes, G, [P] and [P],G genotypes were determined in 93.3%, 95.9%, 93.3%, 73.3%, 95.5% and 92.2% of isolates, respectively. Serotypes G1, G2 and G4 were detected in 58.9%, 30% and 4.4% of the cases, respectively. Rotavirus genotype G5 was detected for the first time in Northern region in 4.4% of the infections. Rotavirus genotypes P[8], P[4], P[6] and P[8+6] were detected in 54.5%, 26.7%, 12.2%, and 2.2% of the cases, respectively. The predominant genotypes were P[8],G1 and P[4],G2 with 53% and 26.6% of the infections, respectively. Unusual strains accounted for 20.5% including P[4],G1, P[6],G1, P[6],G4, P[6],G5, P[8],G2, P[8],G5. Mixed infections involving P[8+6],G2 and P[8+6],G1 were also noted. The neonatal P[6] strains associated with diarrhea were detected among children aged 9-24 months. To our knowledge, this study represents the first in Brazil to analyse, on molecular basis, rotavirus genotypes from children participating in a rotavirus vaccine trial. These results are of potential importance regarding future rotavirus vaccination strategies in Brazil.